Immunomodulators for a Variety of Viral infections of the Skin - Wulan, I G A Kencana; Agusni, Indropo (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: In the last decade there has been inceasing prevalence of viral infections in the world, this led to increased efforts to find a variety of new drugs and vaccines against the virus that causes. Purpose: To disccuss the provision relating to the use of immunomodulators in viral infections. Review: Some diseases caused by viruses such as varicella, herpes zoster, herpes simplex, condyloma acuminata, molluscum contagiosum and Human immunodeficiency syndrome (HIV). Immunomodulator also known as biological response modifier, a wide variety of materials imunoaugmentor is either recombinant, synthetic, or natural medicines that returns an imbalance of the immune system that is used in immunotherapy. Immunotherapy is a treatment approach by restoring, enhancing, or suppresing the immune response. Immunomodulator administration on viral infections gave varying results. Conclusion: Immunomodulatory regimens on viral infections is an attractive therapeutic approach, because the side effects are often lighter than the side effects of drugs that have been there, in addition to the more rarely cause resistance to treatment of diseases caused by viral infection.Key word: viral infection, immunomodulator, immune response.